Involvement of Innate and Adaptive Immune Systems Alterations in the Pathophysiology and Treatment of Depression - Medina-Rodriguez, Eva M.; Lowell, Jeffrey A.; Worthen, Ryan J.; Syed, Shariful A.; Beurel, Eléonore (Frontiers in Neuroscience, 2018)
Major depressive disorder (MDD) is a prevalent and debilitating disorder, often fatal. Treatment options are few and often do not provide immediate relief to the patients. The increasing involvement of inflammation in the pathology of MDD has provided new potential therapeutic avenues. Cytokine levels are elevated in the blood and cerebrospinal fluid of MDD patients whereas immune cells often exhibit an immunosuppressed phenotype in MDD patients. Blocking cytokine actions in patients exhibiting MDD show some antidepressant efficacy. However, the role of cytokines, and the immune response in MDD patients remain to be determined. We reviewed here the roles of the innate and adaptive immune systems in MDD, as well as potential mechanisms whereby the immune response might be regulated in MDD.